การสังเคราะห์งานวิจัยการสอนตามแนวพุทธ: การวิเคราะห์อภิมาน - ทองวิเศษ, พระสันติพงษ์; เนาวนนท์, อดิศร (วารสาร ศึกษาศาสตร์ มมร, 2019)
บทคัดย่อ           การวิจัยครั้งนี้ มีวัตถุประสงค์ของการวิจัยเพื่อศึกษาคุณลักษณะงานวิจัยเกี่ยวกับการสอนตามแนวพุทธ ปีพ.ศ. 2557-2559 ผลการวิจัยพบว่า 1) ผลการวิเคราะห์ข้อมูลด้านคุณภาพวิทยานิพนธ์ที่เกี่ยวกับรูปแบบการเรียนการสอนที่ส่งผลต่อผลสัมฤทธิ์ทางการเรียน เมื่อพิจารณาแบบรายข้อ พบว่า โดยภาพรวมพบว่า อยู่ในระดับดีมาก 2) ผลการวิเคราะห์ข้อมูลด้านคุณลักษณะงานวิจัยที่มีผลต่อค่าขนาดอิทธิพล พบว่า งานวิจัยด้านการสอนตามแนวพุทธเพื่อพัฒนาผลสัมฤทธิ์ทางการเรียนของนักเรียนส่วนใหญ่จะมีค่าขนาดอิทธิพลเป็นลบ ดังนั้น การสอนตามแนวพุทธ จึงช่วยส่งผลต่อ  การพัฒนาผลสัมฤทธิ์ทางการเรียนได้เป็นอย่างดียิ่ง และ 3) การพัฒนาผลสัมฤทธิ์ทางการเรียนของนักเรียนที่เกิดจากการสอนตามแนวพุทธที่นำมาสังเคราะห์มากที่สุด คือ กลุ่มแนวคิดแบบไตรสิกขา ABSTRACT           The objectives of this research are to study the features of research on the teaching following Buddhist way from 2014-2016. The research results reveal that: 1) From the results of data analysis on the quality of theses related to the teaching and learning style affecting the effectiveness of study when each item is considered, it is found that the entire picture is in the excellent level., 2) According to the results of data analysis on the research features affecting the size of influence; it is found that the researches of teaching following Buddhist way for developing the learning efficiency of students has mostly negative influence value. Thus, teaching following Buddhist way can influence the development of learning performance very well., 3) The development of learning performance of students occurs from the teaching following Buddhist way most level. it is found that  the concept group of Traisikka influence.